2011
DOI: 10.1007/s10461-011-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Intervention for Families Living with HIV in Thailand: A Randomized Controlled Trial

Abstract: This study evaluates the efficacy of an intervention for persons living with HIV (PLH) and their family members in Thailand. A randomized controlled trial of 813 PLH and family members was carried out at four district hospitals in Thailand. Participants completed Computer Assisted Personal Interview (CAPI) assessments at baseline, 6, 12, 18, and 24 months. The primary outcome was quality of life (QoL); other measures included depressive symptoms and family functioning. Relative to the standard care condition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Our results resonate with those of other family-focused interventions that have shown promise for HIV-prevention in South Africa [57] and for HIV-affected families in the United States [25,58,59] and Asia [60,61]. The FSI expands upon these important interventions by extending a focus to family-based mental health promotion for school-age children affected by HIV in rural sub-Saharan Africa using a family home visiting model.…”
Section: Discussionsupporting
confidence: 81%
“…Our results resonate with those of other family-focused interventions that have shown promise for HIV-prevention in South Africa [57] and for HIV-affected families in the United States [25,58,59] and Asia [60,61]. The FSI expands upon these important interventions by extending a focus to family-based mental health promotion for school-age children affected by HIV in rural sub-Saharan Africa using a family home visiting model.…”
Section: Discussionsupporting
confidence: 81%
“…We have used this strategy of involving healthcare providers to assist families living with HIV in northern and northeastern Thailand (Li et al, 2010, 2012). The standard of care of providing monthly support groups for PLH in the district hospitals in Thailand facilitates healthcare providers to interact with PLH on a regular basis, and they can play a key role in assisting and supporting PLH with parenting skills.…”
Section: Discussionmentioning
confidence: 99%
“…This study uses data from a randomized controlled family intervention trial in Thailand (Li et al, 2010; Li et al, 2012). Initial screenings of children of PLH were conducted in the district hospitals by healthcare workers and research staff.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature has suggested that HIV disrupts the family structure and places stress on the entire family (Dejman et al, 2015; Li et al, 2012). Since the introduction of antiretroviral therapy (ART), HIV infection has become a lifelong chronic disease (Deeks, Lewin, & Havlir, 2013).…”
Section: Introductionmentioning
confidence: 99%